A young male runner with a posterior knee mass—not just your typical Baker's cyst. (1st March 2016) - Abid, Ayesha; Kelley, James Fitzhugh; Flemming, Donald J; Silvis, Matthew L
Abstract : We present the case of a 28-year-old man with a growing mass in his right popliteal fossa causing pain on exertion. The differential diagnosis included Baker's cyst, entrapment syndrome of the popliteal artery, as well as a benign or malignant neoplasm. An ultrasound was non-specific. Follow-up MRI of the knee demonstrated cystic adventitial disease (CAD). With only about 500 cases reported in the literature since its discovery in 1947, CAD is a rare entity. The disease is characterised by mucinous or gelatinous cysts in the arterial or venous adventitia. The disease is predominantly seen in the popliteal artery and typically affects otherwise healthy males in the fourth to fifth decade of life. It presents clinically as intermittent exertional claudication. Examination of our case and a review of the literature will highlight the importance of considering CAD in patients who report of a popliteal mass and intermittent claudication.